Pengaruh Penggunaan Limbah Plastik LDPE sebagai Modifikator Campuran AC-WC - Amy Wadu; Matheus R Sodanango; Ambrosius L Wayan; Erik E Pello (Borneo Engineering : Jurnal Teknik Sipil, 2023)
In recent years, the increasing amount of plastic waste in many cities in developing countries, including Kupang City, has become a serious environmental problem. The use of plastic waste as a pavement material is one solution to deal with the problem of plastic waste. One type of plastic that can be used as an asphalt mixture modification material is Low Density Polyethylene (LDPE). This research aims to determine the use of LDPE plastic waste modified with AC-WC (Asphalt Concrete-Wearing Course). Five variations of AC-WC mixture were made based on LDPE plastic waste content of 6, 7, 8, 9, 10% based on optimum bitumen content (OBC). Marshall test method was used to determine the OBC and to evaluate the marshall characteristics of LDPE modified AC-WC. The OBC of conventional AC-WC was found to be 5.23% by weight of total aggregate while the ptimum plastic modified bitumen content (OPMBC) of LDPE modified AC-WC was 7.45% by weight of OBC. AC-WC modified with 7.45% LDPE waste had 47.98% higher OPMBC compared to conventional AC-WC